Semantic Analysis in Story Diwa Night: Euphemism and Dysphemism - Cheny Dwi Refita; Khairunnisa Khairunnisa; Delfi Suci Ramadhani; Tiana Mijele (International Journal of Multilingual Education and Applied Linguistics, 2025)
Hikayat Malem Diwa is one of the classic literary works in the Malay-Aceh tradition that is rich in language and cultural values. This story contains various language styles, especially euphemisms and dysphemisms, which reflect social norms, moral values, and conflict dynamics in Acehnese society. This study aims to identify and analyze the forms and functions of these two language styles, emphasizing their semantic and narrative roles. Using a semantic approach and qualitative descriptive methods, data were collected through quotations in the text with documentation techniques, then analyzed based on the context of meaning and use. The results show that euphemisms are often used to convey moral values ​​and politeness, especially in terms of death, respect, and violation of norms. In contrast, dysphemisms appear in the context of violence and character conflict, strengthening the tension and emotion of the story. Overall, the use of these language styles reflects the rhetorical strategies and cultural values ​​of the Acehnese people.